The Analysis of the Formation of the Religious Character of Santri as Memorizers of the Al-Quran at Tahfidz Al-Bayyinah's House - Cendani Alfanizha Hidma; Nurika Khalila Daulay (Edumaspul: Jurnal Pendidikan, 2024)
This article discusses the formation of the religious character of santri which is analyzed based on daily activities that are usually carried out as befits a memorizer of the Al-Quran. Where in its implementation there are interesting problems to be discussed. The aim of this research is to analyze how the religious character of the Al-Bayyinah santri can be formed through habituation from routine activities, discuss who plays a role in forming the religious character of the santri, and discuss what problems there are in forming the religious character of the santri and how to solve them. The type of research used in this research is qualitative research using descriptive methods. The data in this research was obtained through observation techniques, in-depth interviews, and documentation where researchers came directly to the field to obtain research data. The data analysis technique uses the Miles and Huberman method. The results of this research show that the formation of the religious character of students can be formed because it starts with discipline regarding program regulations that have been scheduled, so that this discipline will provide consistency in continuing to do it so that in the end they will get used to continuing to do it. However, in implementation there are also problems caused by several factors, one of which is boredom. From these factors, a solution will emerge, namely approaching the students with several activities such as giving rewards, rihlah (tadabbur nature journey), and other interesting activities.